THE PREVALENCE OF DRUG–DRUG INTERACTIONS OF PRESCRIPTIONS DISPENSED IN COMMUNITY PHARMACIES IN NAJAF CITY-IRAQ - SAMER NOORI HASHIM; MOHAMMED JAWAD SALIH AL-HAIDAREY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The main objectives of this work were to estimate the frequency, type, and nature of possible drug–drug interactions in prescriptions dispensed from community pharmacies in Al-Najaf city, secondary objectives were the study of the association between specialty of physicians and the rate of recurrence of drug–drug interactions and to determine medication classes, which were involved in possible drug–drug interactions. Methods: To investigate this study, 211 prescriptions dispensed in three community pharmacies in Al-Najaf city were collected and by the computerized screening program to identify drug–drug interactions. Results: The results showed that the total number of interactions was recognized to be 41% of all prescriptions with the prevalence of major drug– drug interactions was 14%, minor was 16%, and moderate was 70%. Conclusions: This study concluded that most identified drug–drug interactions were recognized in prescriptions written by an internal medicine specialist, orthopedics, general practitioners, an ear-nose-throat specialist, and general surgeon. The ratio of drug–drug interactions/number of prescriptions increased with increasing the number of drugs prescribed per patient (r=0.93, regression p<0.05). This study suggested that the role of the pharmacist should be moved from medication-oriented to patient-oriented, and the clinical pharmacists should have a vital function in recognizing and avoiding drug–drug interactions in prescriptions dispensed to patients.